Simulation of mobile station location determination using enhanced observed time difference (E-OTD) / Saiful Azhan Hashim - Hashim, Saiful Azhan (2009)
Location Based Services (LBS) is a service provided by cellular radio services due to the location of mobile station (MS). This service was first introduced in Global System for Mobile Communication (GSM) system and it become the most important service in Third Generation (3G) system. There are many techniques to determine mobile station location, such as Global Positioning System (GPS), Angle Of Arrival (AOA), Time Of Arrival (TOA), Time Difference Of Arrival (TDOA), Enhanced-Observed Time Difference (E-OTD) and Cell Global Identity (Cell-ID). But, this paper only discussed about Enhanced-Observed Time Difference (E-OTD) technique. E-OTD used triangulation method and a simulation of this technique was created in MATLAB. This simulation is focused on the location error, which is depend on 2 environments. The environments are urban (error of magnitude, le-7) and rural (error of magnitude, le-9). This simulation also performed comparison between the number of base station (BTS) used.